Airphoto Report: The Vallejo-Mare Island Area - San Francisco Chronicle (San Francisco Chronicle)
Vallejo Next Stop - This is Carquinez Strait where the northern arm of the bay narrows between Contra Costa and Solano counties and is spanned by the great State-owned bridge.